Building Banking Customer Loyalty: The Roles of Product Quality, Customer Service, Operational Excellence, and Work Environment - Rully Armanto; Muji Gunarto; Abdullah Rasjid (Jurnal Nasional Manajemen Pemasaran dan SDM, 2026)
Customer loyalty is a strategic outcome for banks because it reflects trust, repeat use, intention to recommend, and customers' willingness to maintain long-term relationships with financial institutions. This study examines the effects of product quality, customer service, operational excellence, and work environment on banking customer loyalty. The study applies a quantitative explanatory survey design involving 114 banking customers. Data were collected using a structured questionnaire on a five-point Likert scale and analyzed using validity and reliability testing, descriptive statistics, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results show that all research instruments are valid and reliable. Product quality has a positive and significant effect on customer loyalty, indicating that useful, secure, reliable, and easy-to-understand banking products strengthen customer commitment. Customer service also has a positive and significant effect, confirming that responsiveness, empathy, accuracy, and assurance in service encounters are central to customer retention. Operational excellence significantly affects loyalty by ensuring speed, transparency, accuracy, and convenience in banking procedures. The work environment has a positive and significant effect because employee coordination, professional service climate, and adequate service facilities shape customers' service experience. Simultaneously, the four independent variables significantly explain 75.4% of the variance in customer loyalty. The findings imply that banks should not treat loyalty merely as a promotional outcome, but as an integrated result of product relevance, service quality, process reliability, and employee-supportive internal conditions.